The Battle Against Cheating: How Anticheat Systems Shape Gaming - Hossain, Abir (My University, 2025)
The gaming industry has many challenges in ensuring game integrity and player experience, which is especially seen in the online environment. The objective of this thesis is to examine a range of anticheating measures that can be implemented both within and outside of anticheat system. Providing an overview of existing anticheat frameworks, including Valve Anti-Cheat (VAC), Easy Anti-Cheat (EAC), and BattlEye. Focusing on techniques and strategies that is currently used on both the server-side and client-side. The study first looks at the motivations behind cheating activities. Ranging from improving one’s own social status within the community to gaining unfair advantages. Data mining, log analysis, and statistical analysis are used to identify suspicious activities on the server side. The client-side approach includes kernel-level monitoring and file integrity checks to prevent unauthorized modifications. The thesis also highlights the relevance of user authentication methods and CAPTCHA systems, which help protect against bot attacks. Moreover, community-driven approaches, such as player reporting systems, can significantly contribute to creating a positive gaming environment. The topics also includes legal frameworks that explore how cheating is addressed across different jurisdictions. This thesis brings together key insights and approaches to demonstrate the importance of a multilayered strategy in maintaining fairness in the online gaming. The findings suggest that to combat emerging challenges it is necessary to take preventive actions.

Pelialalla on useita haasteita pelien eheyden ja pelaajakokemuksen varmistamisessa, mikä erityisesti koskee verkkoympäristöä. Tämän tutkielman tarkoituksena on tutkia erilaisia huijauksen vastaisia toimenpiteitä, joita voidaan toteuttaa anticheat järjestelmien avulla sekä niiden ulkopuolisilla menetelmillä. Työssä otetaan myös esille olemassa olevat anticheat järjestelmät, kuten Valve Anti-Cheat (VAC), Easy Anti-Cheat (EAC) ja BattlEye. Näiden lisäksi esitellään tekniikoita ja strategioita, joita voidaan hyödyntää anticheat järjestelmien palvelin- ja asiakaspuolella. Turkielma aluksi tarkastelee huijaamisen taustalla olevia motiiveja, jotka vaihtelevat oman sosiaalisen aseman parantamisesta epäoikeudenmukaiseen toimintaan. Näiden toimintojen havaitsemiseksi hyödynnetään palvelipuolella data louhintaa, kirjautumis- sekä tilastollista analyyseja. Asiakaspuolen lähestymistapaan sisältyy kernelin seuranta sekä tiedostojen eheystarkistukset, joiden avulla estetään tiedostojen luvattomat muokkaukset. Tutkielmassa myös korostetaan käyttäjien todennusmekanismeja sekä CAPTCHA järjestelmiä, jotka auttavat bottien torjunnassa. Lisäksi yhteisölähtöiset lähestymistavat, kuten pelaajarapontointijärjestelmät voivat merkittävästi edistää positiivisen peliympäristön luomista. Tutkielmaan sisältyy myös lyhyt katsaus olemassa olevista oikeudellisista toimista eri lainkäyttöalueilla. Tämä opintonäytetyö kokoaa yhteen keskeisiä käsityksiä ja lähestymistapoja huijaamisen estämiseksi sekä korostaa monikerroksisen strategian toteuttamisen tärkeyden peliympäristössä. Työn löydökset viittaavat ennaltaehkäiseviin toimiin nousevien haasteiden torjumeksi.
Keywords: Anti-cheat systems, cheating, motivations, video games,client-side anticheat, server-side anticheat